Fuzzy relational equations - Min-Goguen implication - Zahariev, Zlatko; Zaharieva, Galina; Peeva, Ketty (AIP conference proceedings, 2022)
An algorithm for solving Min-Goguen fuzzy linear systems of equations is presented in this paper. Solving linear systems of equations is subject of great scientific interest. The authors have developed fast an efficient algorithms over several algebras. Here we present, relatively simple, fast and efficient algorithm to solve fuzzy linear systems of equations for Min-Goguen algebra, logically backed by previously developed by the authors algorithms in max-min and min-max algebras.